1994
DOI: 10.1029/94ja02343
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric effects of the March 1990 Magnetic Storm: Comparison of theory and measurement

Abstract: This paper presents a comparison of the measured and modeled ionospheric response to magnetic storms at Millstone Hill and Arecibo during March 16-23, 1990. Magnetic activity was low until midday UT on day 18 when Kp reached 6, days 19 and 20 were quiet, but a large storm occurred around midnight UT on day 20 (Kp=7) and it was moderately disturbed (Kp=4) for the remainder of the study period. At Millstone Hill, the daytime peak electron density (NmFz) showed only a modest 30% decrease in response to the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
2
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 23 publications
(12 reference statements)
7
49
2
4
Order By: Relevance
“…By way of contrast, our observations show an instantaneous or near-instantaneous response (i.e., At=0-2 hours) of haF 2, suggesting that faster mechanisms are in effect (e.g., penetrating electric fields) at least in the first several hours of storm development. Such an instantaneous response in haF,_ was also reported by Richards et al [ 1994]; and studies of the same storm period by Buonsanto et al [1993], using observations at Millstone Hill and Arecibo Observatories, pointed to the importance of penetrating magnetospheric electric fields and disturbance dynamo fields. phase.…”
Section: The Hmf 2 Values Responded Quasi-instantaneously (Or Withinmentioning
confidence: 61%
“…By way of contrast, our observations show an instantaneous or near-instantaneous response (i.e., At=0-2 hours) of haF 2, suggesting that faster mechanisms are in effect (e.g., penetrating electric fields) at least in the first several hours of storm development. Such an instantaneous response in haF,_ was also reported by Richards et al [ 1994]; and studies of the same storm period by Buonsanto et al [1993], using observations at Millstone Hill and Arecibo Observatories, pointed to the importance of penetrating magnetospheric electric fields and disturbance dynamo fields. phase.…”
Section: The Hmf 2 Values Responded Quasi-instantaneously (Or Withinmentioning
confidence: 61%
“…It should be kept in mind that the thermosphere density at satellite heights is mainly presented by [O], and therefore the observed discrepancies with empirical models tell us about the problems with model description of [O] variations. It is known that negative F 2 layer storm effects cannot be satisfactory modeled without special fitting of thermospheric parameters for each particular ionospheric storm, and it has been demonstrated repeatedly [e.g., Richards et al, 1989Richards et al, , 1994bRichards et al, , 1998]. …”
Section: Seasonal Variationsmentioning
confidence: 99%
“…In fact, detailed quantitative studies of ionospheric NmF2 behavior have only recently become meaningful as a result of our development of an algorithm to determine neutral winds that reproduce the observed peak height (hmF2) of the ionosphere [Richards, 1991] [ 1995] all indicated that it may reduce the peak electron density by as much as a factor of 2 in summer at solar maximum. It may also contribute to the negative phase of ionospheric storms [Richards et al, 1989[Richards et al, , 1994bPavlov, 1994]. This paper also presents model results that include the effects of vibrationally excited N2.…”
Section: Introductionmentioning
confidence: 99%